Pro Drupal 7 Development - VanDyk, John; Tomlinson, Todd (Apress : Imprint: Apress, 2010)
Pro Drupal 7 Development updates the most popular development reference for the release of Drupal 7. With several new and completely-rewritten essential APIs and improvements in Drupal 7, this book will not only teach developers how to write modules ranging from simple to complex, but also how Drupal itself works. Learn the Drupal APIs and major changes in Drupal 7 Learn how to write Drupal modules using the APIs Learn proper development practices and how to become a contributing community member.